Six new braconid wasps of the genus Colastomion Baker, 1917 (Hymenoptera: Braconidae: Rogadinae) from Vietnam - Oanh, Nguyen Thi; van Dzuong, Nguyen; Long, Khuat Dang; van Lam, Pham; Nhi, Pham Thi; Hoa, Dang Thi (Zootaxa, 2021)
The relatively small genus Colastomion Baker, 1917 is newly recorded for Vietnam’s braconid fauna and six new species are described and fully illustrated, viz. Colastomion asperum Long, sp. n; Colastomion cephonodes Long & PVLam, sp. n.; Colastomion citrum Long, sp. n.; Colastomion neuterum Long, sp. n.; Colastomion nigroconfusum Long & Pham, sp. n. and Colastomion vietnamenese Long, sp. n. Based on both females and males, a key to the new species from Vietnam is given. Diagnostic characters of the new species are also analyzed and compared with other Colastomion species from the Oriental region. Additionally, the first host record for the new species, C. cephonodes sp. n., is provided as this new species is reared from caterpillars of the coffee hawkmoth, Cephonodes hylas (Linnaeus, 1771).